CORRECTIONAL-LOGOPEDIC WORK ON THE LEXICAL DEVELOPMENT OF SPEECH IN CHILDREN WITH VISUAL IMPAIRMENT - Turdimuratov, Islam Toremuratovich (SCIENCE and SOCIETY, 2026)
This article substantiates the theoretical and methodological foundations of corrective speech therapy for preschoolers with visual impairments and speech underdevelopment. The article validates the need to transition play activity into an educational play format for children with speech disorders. It identifies two levels of linguistic organization –syntagmatic (practical mastery of speech) and paradigmatic (conscious manipulation of language systems) – and shows their sequential acquisition.